1998
DOI: 10.1051/aas:1998461
|View full text |Cite
|
Sign up to set email alerts
|

Long-term spectroscopy of η Carinae

Abstract: Abstract. Quantitative measurements of line parameters in the spectrum of η Carinae are presented for both the broad and narrow line components. A total of 655 spectral features were measured in the spectral range 3850Å to 11000Å, giving a comprehensive view of the behavior of atomic transitions ranging from a few to tens of electron volts. The spectrum on the phase of maximum intensity in the high excitation lines (1995) is compared with that on minimum intensity (June 1992), showing that at this phase the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
71
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(78 citation statements)
references
References 21 publications
7
71
0
Order By: Relevance
“…Damineli (1996) noticed a 5.5 yr periodicity in the spectroscopic variations of He i k10830 emission that correlated with near-infrared photometry (Whitelock et al 1994). Damineli et al (1998) …”
Section: Introductionmentioning
confidence: 62%
“…Damineli (1996) noticed a 5.5 yr periodicity in the spectroscopic variations of He i k10830 emission that correlated with near-infrared photometry (Whitelock et al 1994). Damineli et al (1998) …”
Section: Introductionmentioning
confidence: 62%
“…This turns out to be roughly the centre of the X-ray totality (Corcoran 2003). The R brightness is strongly influenced by the decreasing Hα emission line, which contributed approximately 40% of the total signal of the star at JD 2 452 813, see the substantial change of this line between June 1992 and May 1995 as observed by Damineli et al (1998). Figure 2 shows the V light and colour curves from the UBV data set, and in addition the V − R colour curve.…”
Section: The Bvr Photometrymentioning
confidence: 94%
“…It thus seems that the screening of high-energy photons is the main cause of the decrease of the Hα emission from the outer layers and the wind of the primary (see also Damineli et al 1998). It is tempting to consider the epoch of the R minimum (∼JD 2 452 850) and the mid-X-ray totality, which roughly coincides with the UBV minimum, as the central moment of the PP.…”
Section: Letter To the Editormentioning
confidence: 99%
“…Studies of the binary or binary wind-wind collision zone were reported by many authors (e.g., Damineli 1996;Damineli et al 1997Damineli et al , 1998Damineli et al , 2000Damineli et al , 2008bDavidson 1997;Davidson et al 2005Davidson et al , 2015Smith & Gehrz 2000;Smith et al 2004;Smith 2010;Pittard & Corcoran 2002;Corcoran et al 1997Corcoran et al , 2001Corcoran 2005;Ishibashi et al 1999;Soker 2003Soker , 2007Weis et al 2005;Gull et al 2006Gull et al , 2009Gull et al , 2011Gull et al , 2016Nielsen et al 2007;Weigelt et al 2007; Kashi & Soker 2007, 2009aParkin et al 2009;Groh et al 2010Groh et al , 2012bMadura & Owocki 2010;Madura et al 2012Madura et al , 2013Mehner et al 2010aMehner et al , 2011Mehner et al , 2012Mehner et al , 2015Richardson et al 2010;Teodoro et al 2013Teodoro et al , 2016Clementel et al 2015a,b;Hamaguchi et al 2016). The X-ray...…”
Section: Introductionmentioning
confidence: 99%